Exercise during chemotherapy to prevent breast cancer-related cognitive decline: protocol for a pilot randomized controlled trial - Salerno, Elizabeth A.; Harriss, Courtney; Andrade, D. Carolina; Peterson, Lindsay L.; Duncan, Ryan P.; Kepper, Maura M.; Luo, Jingqin; Creel, Patricia; Colditz, Graham A. (Frontiers in Cognition, 2023)
Background: Cancer-related cognitive decline (CRCD) is one of the most reported debilitating symptoms associated with breast cancer treatment with no currently accepted treatment. Physical activity has emerged as a promising solution for maintaining cognitive health after cancer, with research suggesting that earlier intervention may be important for preventing or mitigating CRCD. There is a clear need to pilot the feasibility and efficacy of pragmatic physical activity interventions to promote cognitive health during active breast cancer treatment. The purpose of this study is to pilot test a home-based prehabilitation physical activity intervention aimed at preventing cognitive decline during chemotherapy, as well as assess the feasibility, acceptability and appropriateness of the intervention among patients. Methods: This study is a two-arm, pilot randomized controlled trial in 40 adult patients newly diagnosed with breast cancer stages I-III who are scheduled to receive curative intent neo-adjuvant chemotherapy. Participants will be randomized 1:1 to a usual care waitlist control group or a home-based prehabilitation physical activity intervention delivered by a licensed physical therapist. The exercise group will receive an individualized, tapered exercise program comprised of home exercise sessions and teleconference coaching calls. Both groups will receive activity monitors and be encouraged to maintain a healthy lifestyle during treatment. Participant adherence and adverse events will be assessed throughout the study. Results: This research was supported by the Alvin J. Siteman Cancer Center through The Foundation for Barnes-Jewish Hospital (award number 6257). The protocol was approved by Washington University’s Protocol Review and Monitoring Committee and Institutional Review Board. Enrollment began in May 2023 and is anticipated to continue through July 2024. Conclusions: This study will provide the necessary preliminary data to support larger trials investigating if and how physical activity can be incorporated into early rehabilitation strategies to prevent chemotherapy-related sequelae.